Airport Management System: Human Resource 1 ( Recruitment, Applicant Management, New Hire On-Board, Performance Management, Social Recognition): Vol. 5, No. 1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Airport Management System has launched a project to implement a new Airline Management System for Human Resource functions. The current manual Human Resource processes will be streamlined and automated using modern technology to create a more efficient and user-friendly system. The initiative is crucial for AMS, aiming to enhance HR operations and improve customer service. The success of the implementation depends on the support of all stakeholders, with a commitment to keeping them informed and engaged throughout the project to align with the company's strategic goals.The project team is implemented systematically, starting with defining project objectives and analyzing requirements collaboratively with stakeholders. It covers features like recruitment, applicant management, onboarding, performance management, and social recognition. The process includes designing a user-friendly interface, developing a robust database, programming modules, and rigorous testing. After deployment, there's ongoing monitoring, support, and emphasis on integration and security. Training sessions ensure effective use, with continuous evaluation and feedback loops. Maintenance addresses update and user feedback for perpetual enhancement.HR 1 department has demonstrated favorable outcomes for stakeholders in airport management. The integration of advanced features such as recruitment, applicant management, onboarding, performance management, and social recognition has optimized human resource processes. This enhancement contributes to efficient HR management, improved employee experiences, and overall satisfaction. Consequently, it is positioned to foster growth opportunities, streamline operations, and modernize human resource practices within the airport, aligning with contemporary industry standards and contributing to the overarching success of airport management operations.HR 1 department module signifies a significant advancement in airport management practices by optimizing human resource processes through streamlined functionalities. Prioritizing a user-centric approach, the module emphasizes integration with existing systems, robust security, and a commitment to continuous improvement. Positioned to enhance operational efficiency, contribute to growth opportunities, and align with organizational objectives, the module plays a crucial role in advancing sophisticated human resource practices in airport management.
Keywords: HR 1